2005
DOI: 10.1038/sj.onc.1208723
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage induce γ-tubulin–RAD51 nuclear complexes in mammalian cells

Abstract: Rad51 protein plays an essential role in recombination repair of DNA double-strand breaks and DNA crosslinking adducts. It is part of complexes which can vary with the stage of the cell cycle and the nature of the DNA lesions. During a search for Rad51-associated proteins in CHO nuclear extracts of S-phase cells by mass spectrometry of proteins immunoprecipitated with Rad51 antibodies, we identified a centrosomal protein, c-tubulin. This association was confirmed by the reverse immunoprecipitation with c-tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
66
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 59 publications
1
66
0
Order By: Relevance
“…47 A direct involvement of RAD51 and paralogues with the centrosome is not yet established but is suggested by the finding that RAD51 can physically interact with γ-tubulin, a centrosome-associated factor. 49 As a second example, while the recombination mediator BRCA2 is predominantly a nuclear factor, a fraction of the BRCA2 pool localizes to centrosomes in the S and early M phases. A reduction in the level of cytoplasmic and hence centrosomal BRCA2 causes centrosome amplification and binucleation of cells.…”
Section: Discussionmentioning
confidence: 99%
“…47 A direct involvement of RAD51 and paralogues with the centrosome is not yet established but is suggested by the finding that RAD51 can physically interact with γ-tubulin, a centrosome-associated factor. 49 As a second example, while the recombination mediator BRCA2 is predominantly a nuclear factor, a fraction of the BRCA2 pool localizes to centrosomes in the S and early M phases. A reduction in the level of cytoplasmic and hence centrosomal BRCA2 causes centrosome amplification and binucleation of cells.…”
Section: Discussionmentioning
confidence: 99%
“…This cell cycle arresting effect clearly suggests that nuclear accumulation of β-tubulin, which does not occur under normal circumstances, is a process of pathophysiological significance and may represent a defense mechanism against stress or malignant transformation. In that respect, it is interesting to note that GFPtagged α-tubulin accumulates reversibly in nuclei of cultured tobacco cells, in response to low temperature (Schwarzerova et al, 2006), whereas nuclear β-and γ-tubulin have been so far detected primarily in cancer or transformed cells (Lesca et al, 2005;WalssBass et al, 2002;Xu and Luduena, 2002;Yeh and Luduena, 2004;.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 4.1R depletion delays transitioning into S phase in untransformed RPE-1 cells, supporting the important role of 4.1R in centrosome structure. Although 4.1R depletion does (1,9,34,45,55). In addition to its functions at interphase centrosomes and in cell cycle regulation, 4.1R is required for formation of mitotic bipolar spindles and for proper cytokinesis.…”
Section: Discussionmentioning
confidence: 99%